Abu Al Qasim Al Zahrawi (Albucasis) and types of his used surgical knives. Issue 4 (4th July 2021) - Khosravi, Azam; Van Hee, Robrecht; Changizi-Ashtiyani, Saeed; Amini, Saeed
Abstract: Background: Surgical incisions require surgical knives. Different surgical knives have been used for surgical practice since its first appearance in surgical science, and evolved according to its progress. Albucasis, Spanish physician (936–1013 AD), is one of the surgical science pioneers whose initiatives in therapeutic and surgical methods are appreciable, as are his surgical instruments including numerous surgical knives. This study aims at thoroughly investigating the appearance, specifications, innovations, and applications of knives in specific surgical techniques. Methods: Volume 30 of the Al-Tasrif li-man ajaza'an al-ta'lif (Al-Tasrif) of Albucasis was complemented with findings in Google Scholar, Ovid, PubMed, Science Direct, and Scopus databases to assess the types of surgical knives used by Albucasis and individualized for different diseases. Results: The majority of the knives in Al-Tasrif have special names such as Mesbar, Maghdah, and Meshel. He chose a special knife dependent on the type of surgery and the incision needed, and adapted the shape of each knife to its use. Conclusions: Albucasis, more than previous physicians, such as Paulus Aegineta (625–690 AD), has invented surgical knives on basis of his own experiences and observations. His accurate knowledge of surgical techniques has resulted in appropriate designing and making functional knives.